Effect of treatment of peripheral arterial disease on the onset of anaerobic exercise during cardiopulmonary exercise testing. Issue 7 (4th April 2021) - Barkat, Mohamed; Key, Angela; Ali, Tamara; Walker, Paul; Duffy, Nick; Snellgrove, Jayne; Torella, Francesco
Abstract: Objective: Cardiopulmonary exercise testing (CPET) is often used to assess pre‐operative fitness in elderly patients, in whom peripheral arterial disease (PAD) is highly prevalent, but may affect the results of CPET by early lactate release due to muscle ischemia. This study investigated the effect revascularization of PAD on oxygen delivery (VO2 ) during CPET. Method: We conducted a prospective cohort study of 30 patients, who underwent CPET before and after treatment of ilio‐femoral PAD. The primary outcome measure was difference in VO2 at the lactate threshold (LT) before and after revascularization. Secondary outcome measures were the relationship between change in VO2 at LT and peak exercise and change in ankle–brachial index (ABI) differential. Results: The study was approved by the North West‐Lancaster Research and Ethics committee (reference 15/NW/0801) and registered in clinicaltrial.gov (reference NCT02657278). As specified in the study protocol, 30 patients were recruited but only 20 (15 men), with a mean age of 62 years, completed pre‐ and post‐treatment CPETs. Twelve patients demonstrated an improvement in VO2 at LT after revascularization, but the difference did not achieve statistical significance (mean difference (95% CI) = 1.43 (−0.21 to 3.08) ml/kg/min; ( p = 0.085). There was, however, a significant improvement in VO2, VE/CO2, workload and Borg breathlessness and leg fatigue score at peak exercise after revascularization. There was no significant correlation between change in VO2 at LT ( r = −0.11, p = 0.65) or change in VO2 at peak and ABI differential ( r = −0.14, p = 0.55). Conclusion: Revascularization of PAD led to significant improvement in multiple peak/maximal exercise parameters within a few weeks and without exercise training. We were unable to demonstrate a statistically significant improvement in VO2 at LT albeit in a majority of subjects this exceeded what we pre‐defined as clinically significant. Abstract : The study suggests that the presence of peripheral artery disease may affect measured oxygen delivery during cardiopulmonary test. Clinical interpretation of this test may need to take into account the presence of occlusive arterial disease of the lower limbs if these results are confirmed.